Pseudomonas sp. STRAIN DSMZ 13134 DAN EFEKTIVITASNYA PADA PERTUMBUHAN TANAMAN TOMAT (Lycopersicum Esculentum Mill. ) SERTA SERAPAN P PADA TANAH MASAM - . A,Aiyen, Johanis Panggeso, Sumarni (AGROTEKBIS, 2015)
A quite big amount of tomato for consumption in Indonesia is still from import. There are two strong challenges on tomato production namely low productivity and pest and diseases. The challenge to improve tomato production becomes stronger if it is planted on acid soil. Acid soil is well known to have low pH which influence on the macro nutrients availability such as N and P. This experiment was aimed to investigate the effectiveness of Pseudomonas sp on tomato growth and P uptake on acid soil. There were 8 treatments tested namely control treatment non-sterilized soil; control sterilized soil;non-sterilized soil + Pseudomonas sp;sterilized soil +Pseudomonas sp;non-sterilized soil + Pseudomonas sp + N, P, K; sterilized soil +Pseudomonas sp + N, P,K; non-sterilized soil + N, P,K ; sterilized soil + N, P, K; and treatment was replicated 3 times. The data was then analyzed with One Way ANOVA and tested by Tukey HSD. Bacteria Pseudomonas sp amendment increased significantly Phosphor (P) concentration, uptake in the shoot of tomato, and triggered the flowering. Amendment of low concentration of N, P, K, together with Pseudomonas sp on acid soil improved significantly tomato growth (plant height, and shoot and root dry biomass), leaf chlorophyll concentration and soil bacteria total colony. The effectiveness of Pseudomonas sp on plant growth was strongly improved when the acid soil microbe diversity was maintained (non-sterilized soil).